Targeting the lncRNA DUXAP8/miR-29a/PIK3CA Network Restores Doxorubicin Chemosensitivity via PI3K-AKT-mTOR Signaling and Synergizes With Inotuzumab Ozogamicin in Chemotherapy-Resistant B-Cell Acute Lymphoblastic Leukemia - Zhang, Li; Zhou, Shixia; Zhou, Tiejun; Li, Xiaoming; Tang, Junling (Frontiers in Oncology, 2022)
Purpose: This study aimed to determine the expression profiles of long non-coding RNA (lncRNA), microRNA (miRNA), and mRNA in chemotherapy-resistant B-cell acute lymphoblastic leukemia (B-ALL). Methods: LncRNA, miRNA, and mRNA profiles were assessed by RNA-seq in diagnostic bone marrow samples from 6 chemotherapy-resistant and 6 chemotherapy-sensitive B-ALL patients. LncRNA DUXAP8/miR-29a/PIK3CA signaling network was identified as the most dysregulated in chemoresistant patient samples and its effect on cellular phenotypes, PI3K-AKT-mTOR signaling and chemosensitivity of doxorubicin (Dox) resistant Nalm-6 (N6/ADR), and Dox resistant 697 (697/ADR) cells were assessed. Furthermore, its synergy with inotuzumab ozogamicin treatment was investigated. Results: 1338 lncRNAs, 66 miRNAs, 1620 mRNAs were found to be dysregulated in chemotherapy-resistant B-ALL in comparison to chemotherapy-sensitive B-ALL patient samples. Through bioinformatics analyses and RT-qPCR validation, lncRNA DUXAP8/miR-29a/PIK3CA network and PI3K-AKT-mTOR signaling were identified as significantly associated with B-ALL chemotherapy resistance. In N6/ADR and 697/ADR cells, LncRNA DUXAP8 overexpression and PIK3CA overexpression induced proliferation and inhibited apoptosis, and their respective knockdowns inhibited proliferation, facilitated apoptosis, and restored Dox chemosensitivity. MiR-29a was shown to affect the lncRNA DUXAP8/PIK3CA network and luciferase reporter gene assay showed direct binding between lncRNA DUXAP8 and miR-29a, as well as between miR-29a and PIK3CA. Targeting lncRNA DUXAP8/miR-29a/PIK3CA network synergized with inotuzumab ozogamicin effect on N6/ADR and 697/ADR cells. Conclusion: Targeting the lncRNA DUXAP8/miR-29a/PIK3CA network not only induced apoptotic effect on Dox-resistant B-ALL and restored Dox chemosensitivity via PI3K-AKT-mTOR signaling but also showed synergism with inotuzumab ozogamicin treatment.